Vertical Prism : A Small Amount Goes a Long Way. - Weigel, Eric (Journal of Behavioral Optometry, 2012)
Background: Patients who present with complaints of headaches, or vague visual symptoms are often the most dif-ficult to manage. A thorough history to explore the nature of the symptoms, including onset, duration, frequency, and severity is essential. Once the more serious differentials have been ruled out, diagnosis and management can be as simple as performing a cover test and prescribing glasses with vertical prism. Three cases will be presented in which vertical prism alleviated the visual symptoms Case Summary: Three patients presented with various complaints of headaches associated with near work that occurred multiple times per week. Entrance testing on all three patients was within normal limits. During cover testing, no movement was seen. However, all three patients reported subjectively noticing a small vertical "phi " motion during cover testing. This "phi " motion was neutralized with small amounts of vertical prism placed before one eye. Each patient was then prescribed the indicated prescription and told to return for a one month follow up appointment. All three patients reported dramatic reduction in the frequency and severity of their headaches at the one month follow up appointment. Discussion: The treatment and management of vertical phorias should be considered when headache/eye strain symptoms are presented. While recent literature related to TBI (Traumatic Brain Injury) demonstrates successful treatment of vertical phorias with prism, the same evidence in the general population is scarce. The purpose of this presentation is to bring light to the topic of small angle vertical phorias, and provide a straight-forward and simple approach for their treatment.